An optimised promoter and signal peptide improves methionine production of a genetically engineered Candida utilis harboring the δ-zein gene - He, Qiburi; Su, Shaofeng; Ao, Riqilang; He, Lingli; Wang, Xiao; Chun, Mei; Gong, Gaowa (Frontiers in Microbiology, 2025)
IntroductionL-methionine is nutritionally indispensable for humans and animals. It is widely applied to feed, livestock and poultry breeding, food, medicine, energy and chemical industries. Maize endosperm contains a stable protein called δ-zein, which is abundant in sulfur amino acids, including methionine. Candida utilis (C. utilis) has been utilized as a cell factory to express and produce recombinant products. However, there is limited information on its genetic background and expression regulatory elements.MethodsIn this study, we aimed to improve methionine yields in an engineered C. utilis harboring the δ-zein gene by identifying a strong promoter and optimal signal peptide. A C. utilis glyceraldehyde-3-phosphate dehydrogenase (GAP) promoter mutant library was constructed and screened to obtain a strong promoter. Subsequently, de novo sequencing of the C. utilis genome was performed using a combination of second-generation Illumina-Seq sequencing platform and third-generation nanopore sequencing technique. Endogenous signal peptides of C. utilis were analyzed by sequencing the C. utilis genome. Recombinant C. utilis strains with homologous integration expression vectors of different signal peptides were constructed and screened for C. utilis optimal signal peptides for secretion of δ-zein.ResultsFinally, a secretory expression system pGS-zein containing a strong promoter GP6 and an optimal signal peptide SP8 was constructed. In the food-grade engineered C. utilis C/pGS-zein methionine content increased by 21.09% compared with that of C/psP with the original promoter, and by 33.64% compared to wild-type C. utilis.DiscussionThis study demonstrates successful expression and secretion of δ-zein in C. utilis and establishes a foundation for enhanced methionine production of heterologous proteins in C. utilis. More importantly, these high-performance biological elements provide fundamental knowledge and technical knowhow for enhanced production of heterologous proteins in C. utilis.